Equity and Justice in Nepal’s School Education System: Policy and Practice Perspectives - Khatri, Pom Bahadur (BMC Research Journal, 2026)
This qualitative study explores the promotion of social justice within the Nepalese education system, focusing on equity in educational access and outcomes across Nepal’s diverse socio-cultural landscape. The research aims to identify existing policy provisions that support social justice in education and to propose actionable strategies for enhancing equity. Utilizing a qualitative approach, data were gathered from various educational policy documents, reports, and scholarly literature, and analyzed through four systematic steps: data collection, interpretation of relevant information, establishment of comparison criteria, and synthesis of findings into conclusions. The analysis revealed three key thematic areas where equity is actively pursued: the implementation of reservation vacancies to ensure representation of marginalized groups (women, Dalits, indigenous communities, and persons with disabilities); the introduction of scholarship schemes and supportive programs (free textbooks, midday meals, and financial aid) to reduce economic barriers; and the promotion of mother tongue education to affirm cultural identity and improve learning outcomes for linguistic minorities. However, challenges persist regarding policy implementation, monitoring, and translating these initiatives into meaningful change. The study concludes that while Nepal has established vital frameworks for inclusive education, advancing true social justice requires strengthened policy enforcement, active community engagement, and the adoption of culturally responsive pedagogy to ensure a truly equitable education system.